Taxonomic updates in Brazilian Stachytarpheta (Verbenaceae) with atropurpureous to black corollas: Two new species and a new synonym - Cardoso, Pedro Henrique; Menini Neto, Luiz; Cabral, Andressa; Trovó, Marcelo (Phytotaxa, 2021)
Stachytarpheta (Verbenaceae) is a genus of shrubs and subshrubs that is centered in Brazil, where 82 species are found. As part of ongoing studies with the genus, we came across two new species of Brazilian Stachytarpheta with atropurpureous to black corollas that are here described and illustrated, Stachytarpheta flavovirescens P.H.Cardoso and Stachytarpheta salimenae P.H.Cardoso & Menini. For each new species we provide photographs, illustrations, phenological information, provisional risk assessments, distribution map, and taxonomic notes. We further synonymize Stachytarpheta dawsonii Moldenke with Stachytarpheta mollis Moldenke, and provide an identification key for the Brazilian Stachytarpheta with atropurpureous to black corollas.